Digital health promotion: promise and peril. (12th December 2021) - Koh, Amanda; Swanepoel, De Wet; Ling, Annie; Ho, Beverly Lorraine; Tan, Si Ying; Lim, Jeremy
Summary: The World Health Organization defines health promotion as process of enabling people to increase control over their health and its determinants, and thereby improve their health. As the world transitions into the information age, incorporating digital technologies into health promotion is becoming commonplace. This article discusses current applications of digital health promotion (DHP) and addresses its potential benefits, challenges, as well as how differences in cultures, governance models and digital readiness across the globe will shape the implementation of DHP differently in each society. The benefits include expanding access to health information and health promoting services, lowering scaling up costs, personalizing health advice and real-time 'nudging' toward healthier options. Key challenges would involve privacy control, appropriate use of data including secondary usage beyond the original intention, defining the limits of 'nudging' and the right of free choice, and ensuring widespread accessibility and affordability to minimize the exacerbation of social inequities. Finally, we discuss the enabling factors for successful DHP implementation, suggesting measures that should be taken at both individual and system levels. At the individual level, we explore the factors necessary to access and benefit from DHP meaningfully; at the system level, we examine the infrastructure required to provide wide access, establish trust among users and enable sustainability of behavioral changes.